Toward Fully Controllable Monomers Sequence: Binary Organocatalyzed Polymerization from Epoxide/Aziridine/Cyclic Anhydride Monomer Mixture - Gao, Tianle; Xia, Xiaochao; Watanabe, Tomohisa; Ke, Chun-Yao; Suzuki, Ryota; Yamamoto, Takuya; Li, Feng; Isono, Takuya; Satoh, Toshifumi (Journal of the American Chemical Society, 2024)
The sequence of monomers within a polymer chain plays a pivotal role in determining the physicochemical properties of the polymer. In the copolymerization of two or more monomers, the arrangement of monomers within the resulting polymer is primarily dictated by the intrinsic reactivity of the monomers. Precisely controlling the monomer sequence in copolymerization, particularly through the manipulation of catalysts, is a subject of intense interest and poses significant challenges. In this study, we report the catalyst-controlled copolymerization of epoxides, N-tosyl aziridine (TAz), and cyclic anhydrides. To achieve this, a binary catalyst system comprising a Lewis acid, triethylborane, and Brønsted base, t-BuP1, was utilized. This system was utilized to regulate the selectivity between two catalytic reactions: ring-opening alternating copolymerization (ROAC) of epoxides/cyclic anhydrides and ROAC of TAz/cyclic anhydrides. Changing the catalyst ratio made it possible to continuously modulate the resulting poly(ester–amide ester) from ABA-type real block copolymers to gradient, random-like, reversed gradient, and reversed BAB-type block-like copolymers. A range of epoxides and anhydrides was investigated, demonstrating the versatility of this polymerization system. Additionally, density functional theory calculations were conducted to enhance our mechanistic understanding of the process. This synthetic method not only provides a versatile means for producing copolymers with comparable chemical compositions but also facilitates the exploration of the intricate relationship between monomer sequences and the resultant polymer properties, offering valuable insights for advancements in polymer science.